2016
DOI: 10.1111/ijpp.12272
|View full text |Cite
|
Sign up to set email alerts
|

“These patients look lost” – Community pharmacy staff’s identification and support of patients with limited health literacy

Abstract: Objective To date, routine use of health literacy assessment in clinical settings is limited. The objective of this study was to explore if community pharmacy staff can identify patients with limited health literacy, how they identify patients and how they support patients to improve medication use. In addition, perceived barriers in providing care for patients with limited health literacy were assessed. Methods Structured face-to-face interviews with pharmacy staff were performed in 27 community pharmacies. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Another limitation of this study is that pharmacists estimated the health literacy level of their patients instead of measuring it with a validated measure, while research has shown that pharmacists find it difficult to estimate the level of health literacy. [39,40] On the other hand, this study showed that pharmacists estimations of the health literacy level of their population did not lead to a selection of the patient population to which the tool was offered, which is in line with the universal precautions approach. Another limitation of this study is that it is unclear to what extent the respondents who volunteered to participate in this study are representative of pharmacists in the Netherlands, limiting the extent to which the results can be generalized to all Dutch pharmacies.…”
Section: Strengths and Limitationsmentioning
confidence: 74%
“…Another limitation of this study is that pharmacists estimated the health literacy level of their patients instead of measuring it with a validated measure, while research has shown that pharmacists find it difficult to estimate the level of health literacy. [39,40] On the other hand, this study showed that pharmacists estimations of the health literacy level of their population did not lead to a selection of the patient population to which the tool was offered, which is in line with the universal precautions approach. Another limitation of this study is that it is unclear to what extent the respondents who volunteered to participate in this study are representative of pharmacists in the Netherlands, limiting the extent to which the results can be generalized to all Dutch pharmacies.…”
Section: Strengths and Limitationsmentioning
confidence: 74%
“…The healthcare professionals described the teachback method through examples from everyday clinical practice. A study has shown that the teach-back method and the use of plain language are techniques reported to facilitate pharmacists' communication with people with low-level HL [34]. Another recent study found positive effects of the teach-back method in enhancing the HL level of 127 older people in a nursing home [35].…”
Section: Discussionmentioning
confidence: 99%
“…The Danish study by Reuther et al (2011) concluded that MDD can be suitable for persons who use several drugs long-term, and whose medication is not changed frequently. The pharmacists interviewed in the study by Koster et al (2016) suggested that the use of aids such as MDD could be a strategy to improve medication use in patients with limited health literacy.…”
Section: Inclusion Of Patients In the Mdd Systemmentioning
confidence: 99%